2013
DOI: 10.1021/jo302763a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Spectroscopic and Electrochemical Properties of an Axially Symmetric Fullerene–Porphyrin Dyad with a Rigid Pyrrolo[3,4-c]pyrrole Spacer

Abstract: A new approach to porphyrinofullerene donor-acceptor dyads, based on consecutive 1,3-dipolar cycloaddition of azomethine ylides, generated from bis-aziridinedicarboxylate, to C60 and to porphyrin with a maleimidophenyl substituent, was developed. A synthesis of the axially symmetric porphyrin-fullerene-C60 ensemble 5 with a novel rigid pyrrolo[3,4-c]pyrrolic linker was realized. Theoretical, electrochemical, and spectroscopic studies of compound 5 showed that it is capable of forming a charge-separated state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…The prerequisite for a successful polymerization process is that the single step in the polymerization chain proceeds with a yield close to quantitative. In our previous study, we found that the reaction of aziridine 3 with maleimide 4 in chlorobenzene under microwave irradiation (45 min, 160 W, maximum temperature reached: 126 °C) gives the expected trans ‐cycloadduct 5 as sole diastereomer in 95% yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The prerequisite for a successful polymerization process is that the single step in the polymerization chain proceeds with a yield close to quantitative. In our previous study, we found that the reaction of aziridine 3 with maleimide 4 in chlorobenzene under microwave irradiation (45 min, 160 W, maximum temperature reached: 126 °C) gives the expected trans ‐cycloadduct 5 as sole diastereomer in 95% yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2s hows ac omparison of UV/Vis spectra of PDI-SiPc (4) and PDI-SiPc-C 60 (1)w itht hose of reference compounds di(pmethylbenzoate)silicont etra-tert-butylphthalocyanine (SiPc-ref; Scheme4)a nd a1 :1 mixture of N,N-di(2'-ethylhexyl) 6,7,4:9, and SiPc-refa ss olutions in benzonitrile.T he reference compounds show typical absorption spectral behaviorf or Pc, C 60 -ref, and PDI. Thus, the spectrumo fP DI-ref features two main absorption bands, with maxima at 489 and 523 nm, andt hat of SiPcref features intense Soret and Q-bands at 363 and 693 nm, respectively.A ll of these bands are common to the absorption spectra of both PDI-SiPc (4)a nd PDI-SiPc-C 60 (1), and the only minor variations in wavelengths indicate an absence of significant electronic interactions betweent he chromophores in the ground state.…”
Section: Opticaland Redox Propertiesmentioning
confidence: 99%
“…Multichromophoric systems that undergo photoinduced electron-and/or energy-transfer processes are of great interest as model photosynthetic systems, [1][2][3][4][5][6][7][8][9][10][11][12] and are potentially useful as active materials in organic photovoltaics (OPV). [1][2][3][4] The use of different buildingb locks, each of which performs ac ertain function, has led to sophisticateds ystemst hat, after excitation of antenna-type subunits,a fford long-lived charge-separated states (CSSs) following as equential mechanism of energy transfer followedby electron transfer.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 ,3 ,4-6 These systems are often composed of C 60 conjugated to planar aromatics to generate molecules in which individual characteristics of the components are often modulated, to give rise to new properties. [8][9][10][11][12][13] It is important to note that one of the highest power conversion efficiencies (PCE) in solutionprocessed organic photovoltaic cells is based on the polymer blends with fullerene derivative as the acceptor component. Importantly, different synthetic strategies have been developed for accessing architectures like C 60 -donor (AD), C 60 -acceptor (AA) or C 60 -donor-C 60 (ADA).…”
Section: Introductionmentioning
confidence: 99%